Caprock Integrity Assessment from Core-Based Formation Analysis and Laboratory Workflow: A Case Study of The Asri Basin Caprock - Buntoro, Aris; Putra, Teddy Eka; Kristanto, Dedi; Swadesi, Boni; Amir, Zulhemi; Lukmana, Allen Haryanto; Wicaksono, Dimas Suryo; Nurcholis, Muhammad (Testing Center for Oil and Gas LEMIGAS, 2026)
Caprock integrity is a critical factor in ensuring the long-term safety of CO₂ geological storage, enhanced oil recovery (EOR), and wellbore stability. This study investigates the sealing performance of shale- and carbonate-rich caprock intervals from the Asri Basin, with specific focus on the Baturaja and Gita Formations. This study introduces a CT-guided integrated laboratory workflow for caprock integrity assessment, which simultaneously links petrophysical sealing capacity, mineralogical controls, and geomechanical strength within a unified experimental framework, a workflow rarely applied in Southeast Asian basins. Whole-core sections from Well ASR-1 were screened using computed tomography (CT) imaging to identify fractures and heterogeneity prior to plug extraction. Laboratory methods included porosity and permeability determination under variable confining stresses, mercury injection capillary pressure (MICP) analysis to evaluate sealing capacity, mineralogical characterization by X-ray diffraction (XRD), scanning electron microscopy (SEM–EDS), petrography, and mechanical testing (UCS, triaxial, and Brazilian tensile tests). The results demonstrate significant depth-dependent variability: The Baturaja Formation exhibited heterogeneous sealing capacity, with entry pressures ranging from 217 to 1,197 psi, while the Gita Formation consistently displayed strong sealing, with maximum Pc_entry of 2,844 psi and pore systems dominated by <0.1 µm throats. Mechanical tests confirmed adequate strength and the preservation of low permeability under confining stress, with clay content and carbonate cementation identified as primary controls on integrity. The integrated workflow enables a process-based interpretation of lithology-controlled sealing mechanisms, improving the robustness of site selection and risk assessment for CO₂ storage in the Asri Basin and similar carbonate and mudstone systems.